(untitled) (Journal of Oriental Studies, 2019)
This article discusses the development of Security Studies and problems associated with the imple- mentation of theoretical experience outside the spread of Western culture, since modern Security Studies are basically built on a Euro-American political culture. In this connection, scientists who study eastern countries, including the Islamic world, often face the problem that existing theories do not always work. This is related to the phenomenon of concept malformation, which was described by the well-known po- litical scientist of the Florentine school of political studies, Giovanni Sartori. Within his theory, the simple implementation of Western concepts in the East leads to a distortion of the results. Scientists propose two ways to solve this problem, which are connected with the search for alternative theories or with the adaptation of existing theories within the region under study. Key words: Security Studies, security, Concept Malformation, theories, Islamic theory of interna- tional relations.